2016
DOI: 10.1155/2016/3948795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Safflower Yellow on the Treatment of Severe Sepsis and Septic Shock: A Randomized Controlled Clinical Trial

Abstract: Objective. To evaluate the clinical effect of safflower yellow on the treatment of severe sepsis and septic shock. Methods. 85 patients with severe sepsis and septic shock were randomly selected to receive either therapy according to the international guidelines for management of severe sepsis and septic shock (Surviving Sepsis Campaign 2012) (control group, n = 45) or conventional therapy plus safflower yellow (study group, n = 40). The 28-day mortality and 28-day Kaplan-Meier survival curves were compared as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Hydroxysafflor yellow A-4 -O-b-D-glucopyranoside and 3 -hydroxyhydroxysafflor yellow A are separated from the SY (Zhang et al, 2020). SY has anti-infection and anti-inflammatory properties, and has been used for the clinical treatment of patients who suffer from severe sepsis and septic shock (Li et al, 2016). Furthermore, SY has anti-fibrotic (Wang et al, 2011), anti-oxidative (Wang et al, 2020), anti-coagulative (Sun et al, 2010), anti-obesity (Yan et al, 2020), anti-calcium-antagonist (Du et al, 2019), and neuroprotective effects (Pang et al, 2020).…”
Section: Safflower Yellow Can Inhibit Inflammatory Reaction the Biological Role Of Safflower Yellowmentioning
confidence: 99%
“…Hydroxysafflor yellow A-4 -O-b-D-glucopyranoside and 3 -hydroxyhydroxysafflor yellow A are separated from the SY (Zhang et al, 2020). SY has anti-infection and anti-inflammatory properties, and has been used for the clinical treatment of patients who suffer from severe sepsis and septic shock (Li et al, 2016). Furthermore, SY has anti-fibrotic (Wang et al, 2011), anti-oxidative (Wang et al, 2020), anti-coagulative (Sun et al, 2010), anti-obesity (Yan et al, 2020), anti-calcium-antagonist (Du et al, 2019), and neuroprotective effects (Pang et al, 2020).…”
Section: Safflower Yellow Can Inhibit Inflammatory Reaction the Biological Role Of Safflower Yellowmentioning
confidence: 99%
“…Our results indicate that HSYA can reduce the release of inflammatory cytokines under septic conditions. Previously, Li et al (2016) have also shown that safflower yellow significantly reduces 28-day mortality and increases survival in patients with severe sepsis and septic shock, and decreasing inflammatory reaction accounts for this protection.…”
Section: Discussionmentioning
confidence: 82%
“…Hydroxysafflor yellow A (CAS number is 78281-02-4) is a major ingredient in safflower yellow, and hydroxysafflor yellow A represents the most abundant and active components in safflower yellow. The main pharmacological effects of safflor yellow A are that it is an antagonist for platelet-activating factor receptor, and platelet-activating factor receptor in the lung tissue of patients with COPD was obviously upregulated [11], which increased airway inflammation, so we used hydroxysafflor yellow A to block upregulated platelet-activating factor receptor in AECOPD, which reduced pathogen adhesion and airway response. Furthermore, T lymphocyte apoptosis was inhibited by safflower yellow [26].…”
Section: Discussionmentioning
confidence: 99%
“…PAF acts not only on platelets but also on leukocytes, endothelial cells, lymphocytes, macrophages, and other cells and participates in the pathophysiological process of allergic asthma, acute inflammation, and other diseases. As a PAF inhibitor, safflower yellow has anticoagulant, anti-inflammatory, vasodilator, and antioxidant effects [811]. The recent research literature has shown that PAF receptor is a specific adhesion point of bacteria on cells, especially common haemophilus influenzae (NTHi) and streptococcus pneumoniae in the respiratory tract, which are prone to adhesion to small airway epithelial cells, the reticular basement membrane, and the alveolar space of COPD patients [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation